2014
DOI: 10.1177/2050640614523596
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the development of oesophageal adenocarcinoma in Barrett's oesophagus: a UK primary care retrospective nested case–control study

Abstract: In this nested case-control study of BO, male gender, increasing age, and increasing use of asthma drugs were associated with progression to OAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
0
13
0
3
Order By: Relevance
“…115 Further, the Northern Ireland Barrett's register reported an approximate 2-fold increased risk of progression from BE to EAC associated with tobacco smoking, 116 a finding confirmed in subsequent smaller cohorts. 117,118 Overall, it is plausible that tobacco smoking contributes to EAC development, given that tobacco is a carcinogen that causes DNA damage in Barrett's epithelium. 119 A recent US study of 81 samples associated tobacco smoking with DNA hypermethylation in esophageal tissues.…”
Section: Tobacco Smokingmentioning
confidence: 99%
“…115 Further, the Northern Ireland Barrett's register reported an approximate 2-fold increased risk of progression from BE to EAC associated with tobacco smoking, 116 a finding confirmed in subsequent smaller cohorts. 117,118 Overall, it is plausible that tobacco smoking contributes to EAC development, given that tobacco is a carcinogen that causes DNA damage in Barrett's epithelium. 119 A recent US study of 81 samples associated tobacco smoking with DNA hypermethylation in esophageal tissues.…”
Section: Tobacco Smokingmentioning
confidence: 99%
“…In einer Fall-Kontroll-Studie entwickelten 55 Barrett-Patienten während eines Follow-ups von 17 743 Patientenjahren ein Adenokarzinom [46]. Daraus berechnete sich eine Karzinomprogressionsrate von 0,3 %/Jahr.…”
Section: Hintergrundunclassified
“…In the PCCIU data, we found b2 agonists, such as salbutamol, were associated with increased risk of oesophageal cancer, results which are consistent with studies by Vaughan et al 16,17,19 Our PCCIU findings are also similar to a recent cohort study of progression from Barrett's oesophagus to oesophageal cancer in which associations were observed with b2 agonist (adjusted HR 1.27, 95% CI 0.68, 2.38) and steroid inhaler use (adjusted HR 2.11, 95% CI 1.12, 3.97), although that study contained a total of only 55 oesophageal cancer cases within their Barrett's oesophagus cohort. 30 The cause of the increased risk of oesophageal cancer with b2 agonist use in PCCIU is unknown. The lack of association in UK Biobank, the lack of dose response association, the association between other asthma medications (e.g., steroidbased) and oesophageal cancer risk provide evidence against a causal interpretation, particularly as several studies have shown marked increases in oesophageal cancer risk in asthma patients.…”
Section: Discussionmentioning
confidence: 99%